SPEAKING INTERACTION PROBLEMS AMONG INDONESIAN EFL STUDENTS - Nurul Fachrunnisa; Nuraeni Nuraeni (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
EFL students have become more prodigious in Indonesia as the use of English has also increased globally at present. EFL students possibly tend to get numerous problems in practising their speaking communicatively. Due to the fact that EFL students are more likely to feel shame to practice their English constantly because of several factors among them. Besides, the use of English does not become habitual on a daily basis and social interaction. The quality of their knowledge of English in the previous study also takes part as the reason why they still have problems in speaking performance. That explanation leads to the speaking problems that arise among the EFL students. This research applied descriptive qualitative research. The participants of this research were the students in majoring the English education program in the 2020/2021 academic year. In this research, the researcher used classroom observation and interviews as the instrument. The interview used a semi-structured interview that was given to the students to see what problems they face during speaking performances and what efforts they have done to solve the problems. From the data analysis, the researcher found that the students have speaking problems in speaking performances in the case of pronunciation, lack of vocabulary and less self-confidence. All of the problems are caused by a lack of practice or interest in studying and memorizing vocabulary. Moreover, the attempts that students take as the solution in solving their speaking problem such as; practising more, increasing vocabulary through memorizing, learning to speak through applications for instance; YouTube, song apps, and Duolingo (English learning application).